Intestinal duplication cyst in the esophagogastric junction as a cause of gastroesophageal reflux disease: a case report - Lara Mejía, Aldo; Alvarez Sores, Erik D.; Gutiérrez Rojas, Carlos A. (International Journal of Research in Medical Sciences, 2023)
This report presents a rare case of a 42-year-old woman with refractory gastroesophageal reflux disease (GERD) attributable to a 5×4 cm enteric duplication cyst at the esophagogastric junction. Despite a year of proton pump inhibitor therapy, the patient experienced persistent symptoms, including nausea and nocturnal vomiting. Surgical intervention involved hiatal plasty, partial Dor fundoplication, and the unexpected discovery of the cystic tumor during the procedure. The cyst, firmly adhered and delimited, ruptured during dissection, leading to successful de-roofing, cauterization, and drainage. The patient’s immediate postoperative course was satisfactory, demonstrating the effectiveness of this approach in managing an enteric duplication cyst. This case underscores the importance of considering congenital anomalies in the context of refractory GERD, with the enteric duplication cyst located at the esophagogastric junction representing a unique manifestation. The study contributes valuable insights into the atypical presentation, diagnostic challenges, and successful surgical management of such anomalies.